Studi Kelayakan Usaha Minuman Jamu Kekinian - Krisnawati Setyaningrum Nugraheni; Dyah Palupiningtyas (Jurnal Publikasi Ilmu Manajemen, 2024)
This research aims to analyze the feasibility of herbal drinks or contemporary jamu business in the scale of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The research method employs both quantitative and qualitative approaches with analysis of market, technical, management, legal, social, and financial aspects. The study results show that contemporary herbal drink businesses have significant market potential with relatively high return on investment, especially when marketed with appropriate branding and targeting millennial and Gen-Z market segments. Financial analysis indicates a payback period of 1.5 years with positive Net Present Value (NPV) and Internal Rate of Return (IRR) of 35%, exceeding the established discount rate. This research concludes that contemporary herbal/jamu drink businesses are feasible to operate as MSMEs by considering appropriate marketing strategies, sustainable product innovation, and compliance with applicable regulations..